Socio-demographic Characteristics of Cataract Patients attended at a Tertiary Care Hospital in Bangladesh (Journal of Science Foundation, 2019)
Background: Cataract is the leading cause for avoidable blindness in the world.Objective: The purpose of the present study was to see the socio-demographic characteristics of cataract patients.Methodology: This cross-sectional study was conducted at National Institute of Ophthalmology, Dhaka, Bangladesh from January 1999 to December 2000 for a period of two (02) years. Patients with senile cataract were selected for study. The details socio-demographic characteristics of the study population were collected which were age, sex, occupation. Data were collected on pre-designed data collection sheet, compiled and appropriate statistical analysis was done using computer based software.Result: A total number of 60 cataract patients were recruited for this study. The mean age with the standard deviation was 58.8±6.055 years. The male and female ratio was 1.31:1. Majority were farmer which was 29(48.3%) cases followed by house wife, grocer and office peon which were 26(43.3%) cases, 4(6.7%) cases and 1(1.7%) case respectively. Most of the patients were from poor socio-economic condition which was 34(56.7%) cases. Majority of the patients were illiterate which was 47(78.3%) cases.Conclusion: In conclusion old age male patients coming from poor socioeconomic condition are the most commonly affected by cataractJournal of Science Foundation 2018;16(2):45-48